2011
DOI: 10.1007/s00167-011-1653-3
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring graft sizes differ between Chinese and Caucasians

Abstract: Prospective cohort study (prevalence), Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 22 publications
7
43
1
Order By: Relevance
“…A similar correlation was found by other studies with smaller and/or non-Caucasian populations [5, 10, 24, 29, 32, 36, 38]. Chiang et al [5] studied a group of 100 Chinese patients and found a significant correlation between height and length of both semitendinosus and gracilis tendons after multiple linear regression analysis. The authors compared their data to the study population by Treme et al and concluded that Caucasian patients had significantly longer hamstring tendons compared to the Chinese Han population [5, 36].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A similar correlation was found by other studies with smaller and/or non-Caucasian populations [5, 10, 24, 29, 32, 36, 38]. Chiang et al [5] studied a group of 100 Chinese patients and found a significant correlation between height and length of both semitendinosus and gracilis tendons after multiple linear regression analysis. The authors compared their data to the study population by Treme et al and concluded that Caucasian patients had significantly longer hamstring tendons compared to the Chinese Han population [5, 36].…”
Section: Discussionsupporting
confidence: 81%
“…Various authors have analysed the predictability of hamstring tendon dimensions by anthropometric parameters [2, 4, 5, 10, 16, 18, 2427, 29, 31, 32, 3538]. Some studies analysed graft diameter [2, 4, 18, 25, 27, 35, 37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is in agreement with the study done in Singapore, which stated that height, weight, and BMI is not a reliable variable to predict hamstring autograft size. The differences in these findings may be due to the differences in ancestral lineage [13,21].…”
Section: Discussionmentioning
confidence: 90%
“…Relative lengths of limbs used for the study were in the range of anthropological characteristics for white Caucasian population; therefore, limited number of investigated specimen does not affect the importance of obtained results [6,10].…”
Section: Discussionmentioning
confidence: 99%